Parental preference for influenza vaccine for children in China: a discrete choice experiment - Gang Chen; Ping Liu; Xiaochen Ma; Hai Fang; Zhiyuan Hou; Hongguo Rong; Xiaozhen Lai; Shunping Li; Tiantian Gong (BMJ Open)
Objectives To investigate what factors affect parents’ influenza vaccination preference for their children and whether there exists preference heterogeneity among respondents in China.Design Cross-sectional study. A discrete choice experiment was conducted. Five attributes were identified based on literature review and qualitative interviews, including protection rate, duration of vaccine-induced protection, risk of serious side effects, location of manufacturer and out-of-pocket cost.Setting Multistage sampling design was used. According to geographical location and the level of economic development, 10 provinces in China were selected, and the survey was conducted at community healthcare centres or stations.Participants Parents with at least one child aged between 6 months and 5 years old were recruited and the survey was conducted via a face-to-face interview in 2019. In total, 600 parents completed the survey, and 449 who passed the internal consistency test were included in the main analysis.Main outcomes and measures A mixed logit model was used to estimate factors affecting parents’ preference to vaccinate their children. In addition, sociodemographic characteristics were included to explore the preference heterogeneity.Results In general, respondents preferred to vaccinate their children. All attributes were statistically significant and among them, the risk of severe side effects was the most important attribute, followed by the protection rate and duration of vaccine-induced protection. Contrary to our initial expectation, respondents have a stronger preference for the domestic than the imported vaccine. Some preference heterogeneity among parents was also found and in particular, parents who were older, or highly educated placed a higher weight on a higher protection rate.Conclusion Vaccination safety and vaccine effectiveness are the two most important characteristics that influenced parents’ decision to vaccinate against influenza for their children in China. Results from this study will facilitate future policy implementations to improve vaccination uptake rates.